Evaluation Of Information System Governance Capability Level Of Engineering Construction Services Firm Using COBIT Framework 5 - Adi Nugroho, Wisnu; Sutomo, Rudi (Publisher Cv. Inara, 2023)
Engineering Construction Services Firm Instrument Engineering is a company in engineering construction services. Not only construction services Engineering Construction Services Firm Instrument Engineering also has services in the field of non-construction such as operation and maintenance. There is no quality management standard in the company expected to increase productivity and superiority over competitors; the company needs a schedule to conduct periodic audits of information security management. It requires recommendations for improving the Information Security Management System), and the company hopes to make a standard document for data and information security risk governance aimed at supervision and review of the Information Security Management System. To make sure that SI operations within the Company have been carried out and objectives have been supported as effectively as possible, it is required to conduct an information system audit using the Control Objectives for Information and Related Technology (COBIT) framework based on the needs that have been described. The research on evaluating IT governance abilities using the COBIT 5 framework APO13 process ends at level 1 with a status of 82.12. EDM03 and APO12 processes terminate at level 2, with a Largely achieved status of 82.12 for EDM03 and 84.41 for APO12.